No guarantees - Lanham, Cheryl (New York : Berkley Books, 1997)
Courtney is excited about the beginning of the new school year. She has great friends, cool clothes, and just about anything money can buy. She even made the cheerleading squad. Suddenly all of Courtney's plans vanish when her father loses his job and her parents reveal they are flat broke. Instead of buying her cheerleader's uniform, Courtney now must find a job to help her family get by.
"Young adult novel"--Spine.
Keywords: Teenagers -- Fiction